Mitigation of cold stress in red female betta (Betta splendens) through dietary supplementation with annatto (Bixa orellana L.) oil extract - Dorce, Larissa Selini; do Couto, Márcia Valéria Silva; da Silva, Weliton Vilhalba [UNESP]; Siqueira, Mayara Schueroff; do Carmo Ota, Erika; Saturnino, Klaus Casaro; Scardua, Marcos Paiva; Neu, Dacley Hertes; Martelli, Silvia Maria; Honorato, Claucia Aparecida (Springer Nature, 2025)
This study aimed to evaluate the effects of using annatto oil extract in the diet of red Betta splendens females subjected to temperature stress. A total of 150 juveniles (initial weight 0.997 ± 0.038 g and 3.909 ± 0.268 cm) were used, randomly distributed in 15 aquariums (20 L). The fish were fed for 28 days with diets containing increasing levels of annatto oil extract: 0.00; two; 4; 6- and 10-mL.kg−1 diet. In the end, all individuals were submitted to a decrease in temperature and maintenance in the cold, then passed the recovery test, remaining for 6 h at low temperatures. No differences were observed regarding animal performance and survival. The oily extract did not change digestive and liver functions and skin color. The use of 2 and 10 mL promoted an increase in superoxide dismutase activity in the skin of fish submitted to a decrease in temperature. The use of 2 and 4 mL decreased catalase activity in the skin. High levels of oil extract increased gill catalase activity in temperature recovery. It is concluded that 10 ml of annatto oil extract is efficient in mitigating the effects of low-temperature stress in Betta splendens females.
Keywords: Functional foods; Ornamental fish; SOD; Temperature stress; Urucum